Endometrial metastasis of colorectal cancer with coincident endometrial adenocarcinoma. (5th November 2010) - Colling, Richard; Lopes, Tito; Das, Nagiindra; Mathew, Joe
Abstract : Metastasis to the uterine corpus is uncommon and secondary colorectal tumours of the endometrium are rare. We describe a uterine tumour with components of both primary endometrial and metastatic colorectal carcinomata. In this case, a 72-year-old obese woman presented with a 2-week history of postmenopausal bleeding per vaginum and weight loss. She had an abdominoperineal resection 3 years previously for a Dukes stage B rectal carcinoma. A transvaginal ultrasonography showed a thickened endometrium. Histology immunophenotyping showed a CK7+, CK20+, CA125− and CEA+ colorectal metastasis (a profile consistent with her previous cancer) associated with a primary CK7+, CK20−, CA125+ and CEA− endometroid endometrial adenocarcinoma. We conclude this represents endometrial metastasis of colorectal carcinoma with coincident primary endometrial adenocarcinoma. We speculate as to whether the endometrial carcinoma arose de novo or was induced by the colorectal metastasis, or whether the primary endometrial tumour provided a fertile site for the colorectal metastasis.